Achilles Tendon Rupture Treatment Systematic Review and Meta-analysis - Sara España Fernández de Valderrama MD; Beatriz García Martínez MD; Laura Ezquerra Herrando MD, PhD (Foot & Ankle Orthopaedics)
Background: Acute Achilles tendon rupture (ATR) has increased in recent decades, reflecting the longer life expectancy and higher levels of activity. Surgical intervention has been the main treatment, but recently there has been growing interest in nonoperative approaches. Study compares surgical and conservative treatment of acute ATR, examining demographic data, rerupture rate, complications, and functional scale Achilles Total Tendon Rupture Score (ATRS). Methods: A literature review was conducted including randomized clinical trials and prospective cohorts. RevMan software was employed to ascertain the I ² heterogeneity, with a view to determining whether a fixed or random effects model should be used for meta-analysis. The results were expressed as either the mean difference or relative risk (RR), as appropriate, with 95% CI. Results: Ten studies, published after 2010, were included in the analysis. Of the total 1327 participants, 57.8% received surgical treatment and 42.2% nonsurgical treatment. The follow-up was between 12-24 months. The rerupture rate was lower in surgical treatment (RR 0.28, 95% CI 0.15-0.50; P  < .0001), although this was accompanied by a higher risk of complications (RR 2.39, 95% CI 1.57-3.63; P  < .0001). The patient satisfaction was comparable between the 2 treatment groups, with no statistically significant difference on the ATRS scale (MD 0.87, 95% CI –1.18 to 2.92; P  = .40). Conclusion: Surgical repair of acute ATR significantly reduces the risk of rerupture but it is associated with a higher rate of complications. Furthermore, there are no significant differences in the various functional scales in terms of patient satisfaction between the 2 treatments. Level of Evidence: II, meta-analysis